The ventriculocholecystic shunt: two case reports and a review of the literature. (August 2013) - Demetriades, A. K.; Haq, I. Z.; Jarosz, J.; McCormick, D.; Bassi, S.
Abstract: We describe the re-siting of ventriculoperitoneal shunts to the gallbladder in two children. The first child had a rare case of hydrocephalus associated with plasminogen deficiency. She had had multiple VP shunt revisions due to non-absorption of CSF from the peritoneum. The second had craniopharyngioma-related hydrocephalus with once again a non-absorbing peritoneum. We report no surgical complications in the revisions for both the cases, and there has been a subsequent follow-up of 46 and 28 months, respectively, without incident. A review of the relevant literature describing the use and the performance of ventriculocholecystic shunts in comparison with other ventricular shunts is considered.